Risky business: rhesus monkeys exhibit persistent preferences for risky options - Xu, Eric R.; Kralik, Jerald D. (Frontiers in Psychology, 2014)
Rhesus monkeys appear to prefer risky over safe options in experiential decision-making tasks. These findings might be due, however, to specific contextual factors in the tasks used to date, such as a large number of successive trials and small ‘stakes’, i.e., small amounts of fluid reward. In the present experiment, we increased the stakes and used a small number of trials in order to explore the generality of risky decision-making in monkeys. We found a consistent preference for risky options, except when the expected value of the safe option was greater than the risky option. Thus, with equivalent mean utilities between the safe and risky options, rhesus monkeys appear to have a robust preference for the risky options in a broad range of circumstances, akin to the preferences found in human children and some adults in similar tasks. One account for this result is that monkeys make their choices based on the salience of the largest payoff, without integrating likelihood and value across trials. A related idea is that they fail to override an impulsive tendency to select the option with the potential to obtain the highest possible payoff. Our results rule out both accounts and contribute to an understanding of the diversity of risky decision-making among primates.